2000
DOI: 10.1073/pnas.060023897
|View full text |Cite
|
Sign up to set email alerts
|

AiiA, an enzyme that inactivates the acylhomoserine lactone quorum-sensing signal and attenuates the virulence of Erwinia carotovora

Abstract: N-acylhomoserine lactones, known as autoinducers (AIs), are widely conserved signal molecules present in quorum-sensing systems of many Gram-negative bacteria. AIs are involved in the regulation of diverse biological functions, including expression of pathogenic genes in the plant pathogens Pseudomonas solanacearum, several Erwinia species, and the human pathogen Pseudomonas aeruginosa. A bacterial isolate, Bacillus sp. 240B1, is capable of enzymatic inactivation of AIs. The gene (aiiA) for AI inactivation fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
543
0
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 477 publications
(564 citation statements)
references
References 32 publications
(19 reference statements)
14
543
0
7
Order By: Relevance
“…Although the aiiA gene did not share significant homology with any known sequences, it did encode an HXHXD sequence motif common to metallo-␤-lactamases. Purified AiiA protein inactivated multiple AHLs in vitro (57), and biochemical analysis confirmed that AiiA functioned as a lactonase (85). Importantly, when cloned into the plant pathogen Erwinia carotovora, the aiiA gene reduced AHL release from the pathogen, decreased QS-controlled enzyme activities, and reduced soft rot disease symptoms on potato, eggplant, Chinese cabbage, carrot, and celery plants (57).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 98%
See 3 more Smart Citations
“…Although the aiiA gene did not share significant homology with any known sequences, it did encode an HXHXD sequence motif common to metallo-␤-lactamases. Purified AiiA protein inactivated multiple AHLs in vitro (57), and biochemical analysis confirmed that AiiA functioned as a lactonase (85). Importantly, when cloned into the plant pathogen Erwinia carotovora, the aiiA gene reduced AHL release from the pathogen, decreased QS-controlled enzyme activities, and reduced soft rot disease symptoms on potato, eggplant, Chinese cabbage, carrot, and celery plants (57).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 98%
“…AHL lactonases are metalloproteins (with the exception of AiiM) that hydrolyze the ester bond of the homoserine lactone ring to yield the corresponding acyl homoserine molecule (Fig. 3) (57,85). Hydrolysis of this ester bond can also occur spontaneously at alkaline pH, and acidic conditions can restore the bond and AHL signaling activity following biological or abiotic hydrolysis (86).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 99%
See 2 more Smart Citations
“…and other species [9,[12][13][14]. Genetically-modified Erwinia carotovora and Pseudomonas aeruginosa expressing AHL-lactonase showed decreased production of virulence factors and attenuated virulence [15,16]. AHL-lactonase has been over-expressed successfully in E. coli and Pichia pastoris expression system as a soluble heterologous protein [17,18].…”
Section: Introductionmentioning
confidence: 99%